Colchicine Intoxication in Children: Four Case Reports - Ayşenur P. KISAARSLAN,; Sibel YEL,; Kenan YILMAZ,; Başak Nur AKYILDIZ,; Ruhan DÜŞÜNSEL,; Zübeyde GÜNDÜZ,; Hakan POYRAZOĞLU,; Gül YÜCEL,; Feride GÜVEN, (Archives of Rheumatology, 2015)
Colchicine is a natural alkaloid which is derived from the colchium autumnale plant. It is used in the treatment of familial Mediterranean fever, amyloidosis, gout, Behçet’s disease, and inflammatory bowel disease. In this article, we present four colchicine intoxication cases who were admitted to our clinic last year. While two patients ingested colchicine accidentally, other two took it for attempted suicide. First patient’s clinical signs were gastroenteritis, fever, and alopecia. This patient developed renal, hepatic dysfunction, and rebound leucocytosis. Patient was given support treatment and discharged. Second patient’s physical examination was normal except for tachycardia. Twenty hours after taking the medication, patient developed leucocytosis. The patient was performed plasmapheresis and leukapheresis. Thirty-nine hours after intake, patient developed sudden cardiac arrest and died. Third patient’s clinical signs were gastroenteritis, fever, and alopecia. Patient developed hepatic dysfunction and rebound leucocytosis. Support treatment was given and patient was discharged. Last patient had no clinical sign or laboratory finding and was discharged. Doctors and other healthcare employees should be alert for possible colchicine intoxication symptoms. Early detection of overdose symptoms is significant in terms of treatment success.